Network coding : fundamentals and applications - Médard, Muriel; Sprintson, Alex.; ScienceDirect eBooks (London : Academic, 2010)
Network coding is a field of information and coding theory and is a method of attaining maximum information flow in a network. This book is an ideal introduction for the communications and network engineer, working in research and development, who needs an intuitive introduction to network coding and to the increased performance and reliability it offers in many applications. This book is an ideal introduction for the research and development communications and network engineer who needs an intuitive introduction to the theory and wishes to understand the increased performance and reliability it offers over a number of applications. A clear and intuitive introduction to network coding, avoiding difficult mathematics, which does not require a background in information theory. Emphasis on how network coding techniques can be implemented, using a wide range of applications in communications and network engineering Detailed coverage on content distribution networks, peer-to-peer networks, overlay networks, streaming and multimedia applications, storage networks, network security and military networks, reliable communication, wireless networks, delay-tolerant and disruption-tolerant networks, cellular and ad hoc networks (including LTE and WiMAX), and connections with data compression and compressed sensing Edited and contributed by the world's leading experts.
Introduction -- Network coding Fundamentals -- Harnessing Network Coding in Wireless Systems -- Network Coding for Content Distribution and Multimedia Streaming in Peer-to-Peer Networks -- Network Coding in the Real World -- Network Coding and User Cooperation for Streaming and Download Services in LTE Networks -- CONCERTO: Experiences with a Real-World MANET System Based on Network Coding -- Secure Network Coding: Bounds and Algorithms for Secret and Reliable Communications -- Network Coding and Data Compression -- Scaling Laws with Network Coding -- Network Coding in Disruption Tolerant Networks.
Print version record.
Elsevier
Keywords: Coding theory; Data transmission systems; Computer networks -- Mathematical models; Coding theory; Computer networks -- Mathematical models; Data transmission systems; Electronic books